Bioclimatic features of Toruń according to the tourism climate index - Derkowska, Izabela; Araźny, Andrzej (Bulletin of Geography. Physical Geography Series, 2022)
The paper characterises the annual pattern and the long-term variability of the Tourism Climate Index (TCI) in Toruń in the years 1966–2020. In the annual variation, conditions for tourism and recreation were best from May to August. For the summer period (from June to August), the climatic conditions according to TCI were excellent, while for May they were assessed as very good. Meanwhile, the least favourable conditions for recreational and tourist activity occur in the winter months of January and December. In Toruń, there was a statistically significant increase of 0.9 pt/10yr in the annual average TCI value. An improvement in climatic conditions for humans was demonstrated for all seasons but was greatest in spring and autumn (respectively 1.6 and 1.0 TCI pt/10yr). Atmospheric circulation was also found to affect TCI. This was determined using a calendar of circulation types over central Poland, based on which indices of zonal, meridional and cyclonic circulation were used. The study has shown that anticyclonic circulation has the greatest impact on improving conditions for tourism.